ANALYSIS OF THE EFFECTS OF INTERNAL AND EXTERNAL FACTORS TO THE DETERMINATION OF THE INTEREST RATE POLICY OF TERM DEPOSIT IN PRIVATE NATIONAL BANKS IN INDONESIA IN 2010-2014 - Purnamayanti, Ayu Rizki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
ABSTRACTThe interest rate shows how much benefit that will be earned on funds entrusted by clients to banks with maturities in accordance with the agreement that has been agreed upon. The longer the term of the deposit, the higher the interest rates on deposits. However, banking conditions that often experience changes cause fluctuations in interest rates on term deposits of the National Private Banks in Indonesia. Hence, the level of the highest deposit rates are at a 3-month period compared to a period of 6 months and 12 months. This study is aimed to analyze the effect of inflation, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Return on Assets (ROA) of the interest rates on term deposits of the National Private Banks in Indonesia that are amounted to 60 banks. The method used is multiple linear regression with time series method using SPSS 20.The results showed that inflation and LDR variables have positive effects while CAR has negative effects on the determination of interest rate policy on deposits. In this study, there is a variable that is unrelated, which is ROA, but this variable is able to explain why there is no correlation due to the policy of the National Private Banks.Keywords: Interest Rates of Term Deposits, Inflation, CAR, ROA, LDR